Understanding Investment Analysis for Farm Management - Julio Cruz; Ariel Singerman (EDIS)
Investment decisions are among the most important decisions growers make. In many cases, those investments are in capital assets such as establishing a new orchard or purchasing a new piece of equipment. The process for evaluating those investments is called investment analysis or capital budgeting. This 4-page fact sheet written by Julio Cruz and Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department reviews net present value and the internal rate of return, the two main criteria for decision making when evaluating a decision to invest in a capital asset. https://edis.ifas.ufl.edu/fe1060